2011
DOI: 10.1016/j.bodyim.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Salience of physical appearance characteristics among young women in Thailand

Abstract: Our aim in the present study was to identify key components of physical appearance among young Thai women. Free listings, focus groups and pile sorting were used. One-hundred twenty young women generated 78 unique physical appearance characteristics. Ninety-four nursing students validated these characteristics in focus groups and then sorted them into piles that reflected separate domains of physical appearance and labeled them. Salience analysis revealed that facial appearance (e.g., bright facial skin, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
(83 reference statements)
2
7
0
Order By: Relevance
“…This was reflected in our finding that White Americans who were high in body dissatisfaction were also high in excessive exercise. On the other hand, Asian women were more concerned about being thin rather than having a fit body (Kaneko, Kiriike, Ikenaga, Miyawaki, & Yamagami, 1999;Rongmuang et al, 2011). The preceding finding was true in our study as well, where international Vietnamese women who were high in body dissatisfaction also restricted their food intake.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…This was reflected in our finding that White Americans who were high in body dissatisfaction were also high in excessive exercise. On the other hand, Asian women were more concerned about being thin rather than having a fit body (Kaneko, Kiriike, Ikenaga, Miyawaki, & Yamagami, 1999;Rongmuang et al, 2011). The preceding finding was true in our study as well, where international Vietnamese women who were high in body dissatisfaction also restricted their food intake.…”
supporting
confidence: 79%
“…Our results extended the literature by providing evidence for potentially differing cultural values with regard to the thin ness ideal between international Vietnamese and White American female undergraduates. Previous crosscultural research on perceived physical attractiveness revealed that women from Asian countries had a considerably lower idealized body size compared to Western standards (Lee, Leung, Lee, Yu, & Leung, 1996;Rongmuang et al, 2011). Interestingly, Wardle et al (2006) examined body image and weight control across several countries in Europe, the Mediterranean, Pacific Asia, and the Americas, and found that women from Asian countries had the lowest body mass index but reported the highest levels of weight concerns and perceptions of being overweight.…”
mentioning
confidence: 99%
“…Furthermore, while we added three items to the original body dissatisfaction scale we used based on the literature on Asian males, it is possible that other body features may also be important. For example, skin tone and texture may be important determinants of body dissatisfaction among Asian populations (Rongmuang et al, 2011). Future assessments of the determinants of body dissatisfaction among adolescent males could include assessment of other such potentially relevant traits.…”
Section: Discussionmentioning
confidence: 99%
“…Another body feature that may hold significance for Asian adolescent males, although it has received very little research attention, is dissatisfaction with hair. Research suggests that hair dissatisfaction may be an important feature of body dissatisfaction among Asian women (Mellor et al, 2013; Rongmuang et al, 2011; Tewari, 2009), and results from recent qualitative research suggests that this may also be the case for young adult Asian males (Watt & Ricciardelli, 2012). Watt and Ricciardelli (2012) reported that hair-change strategies, such as styling and coloring, emerged as a theme in discussions about body image with male Chinese participants, and intracultural variations were also reported, with Japan, Korea, and Hong Kong being identified as the “harbingers of hair fashion” for Asian men (p. 121).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by empirical data showing a relatively standardised preference for female thinness and similar rates of actual-ideal weight discrepancy across nations (e.g., Swami, Frederick et al, 2010). Similar processes have not been examined vis-à-vis breast size, although some scholars have suggested the increasing commodification and objectification of large breasts in some parts of the world (e.g., in East and Southeast Asia; Rongmuang et al, 2011;Wong, 2019), as well as a marked shift away from a focus on the functions of the breasts toward their treatment in purely aesthetic terms (Miller, 2006). In the absence of empirical data, however, it is difficult to know to what extent a homogenising pattern could be observed globally, and so a first aim of the present study was to examine breast size ideals and breast dissatisfaction across diverse national sites.…”
Section: Breast Size and Dissatisfactionmentioning
confidence: 94%